Outdoor wind behaviour and wind comfort of coastal resorts in Malaysia / Wan Mohd Taufiq Wan Jabarudin - Wan Jabarudin, Wan Mohd Taufiq (2016)
The existence of buildings inevitably changes the external micro-climate within the surrounding where the wind pressure, wind speed and air temperature are the main driving forces. Planning factors should not only focus on improving indoor air condition but to include its effect on the outdoor environment particularly exploiting the wind for pedestrian wind comfort and safety. This aim of the study is to supplement knowledge on the prediction of the outdoor wind behaviour as an improvement to pedestrian comfort using wind forces in buildings along coastal regions of Malaysia. The objectives set out to study on the wind behaviour around the building and the wind effect on human achieving outdoor comfort and suggesting a suitable planning layout based on the study. This research scope focus on the outdoor wind around the beach resort which was used as the case studies and their layouts were remodelled and simulated using PIV in the wind tunnel and CFD. The microclimates data taken from meteorological station and data for surrounding surface roughness for coastal area were used to simulate boundary condition. The case studies namely, Merang Sutra Beach Resort (MSBR), Sematan Palm Beach Resort (SPBR) and Lexis Port Dickson (LPD differ from one another in terms of building arrangement, geographical locations and prominent wind directions. The result on Discomfort Indoor and Outdoor Probability indicated that wind is sufficient to achieve the outdoor wind comfort. However, it does not conform in long exposure areas where the hourly wind speed probability be less than 80% acceptability. The Pmax for Safety and Wind danger indicates that the wind is still in preferable condition. The conclusion drawn from the PIV simulation showed the channelling of wind between buildings resulted in an increase in velocity. In most cases, a suitable layout for beach resort face prevailing wind from the sea, but, in some region, the prevailing wind comes from the land. It is recommended that a study on the microclimate need to be carried out on the new development for sustainability.